The Potential of Halal Culinary Tourism Among Non-Muslim Communities in Bali - Rokhmat Subagiyo; Achmad Syaichoni (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThe development of halal culinary tourism in Indonesia as a whole is quite significant. However, the application of halal cooking in the Bali region is still limited. The aim of this research is to determine the development of halal culinary tourism for non-Muslim communities in Bali. This research uses a qualitative descriptive research method. Data collection, both primary and secondary, is carried out through interviews, observation and documentation. SWOT analysis has used to take the conclusions about existing research problems. The research findings show several discoveries, including providing high-quality halal food to attract more tourists; diversifying the halal culinary menu with local nuances in tourist areas; continuing collaboration with local food producers and farmers to obtain environmentally friendly raw materials; expanding partnerships with other local and regional businesses; and increasing efforts to promote halal food by organizing events with local communities, including non-Muslims.Keywords: Halal Tourism; halal culinary; non-Muslim societyÂ Abstrak Perkembangan wisata halal di Indonesia cukup signifikan. Namun penerapan masakan halal di wilayah Bali masih terbatas. Tujuan penelitian ini adalah untuk mengetahui potensi wisata kuliner halal bagi masyarakat non muslim di Bali. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Pengumpulan data, baik primer maupun sekunder, dilakukan melalui wawancara, observasi, dan dokumentasi. Analisis SWOT digunakan untuk menarik kesimpulan terhadap permasalahan penelitian yang ada. Temuan penelitian menunjukkan beberapa penemuan, antara lain menyediakan makanan halal berkualitas tinggi untuk menarik lebih banyak wisatawan; diversifikasi menu kuliner halal bernuansa lokal di kawasan wisata; melanjutkan kolaborasi dengan produsen pangan dan petani lokal untuk mendapatkan bahan baku ramah lingkungan; memperluas kemitraan dengan bisnis lokal dan regional lainnya; dan meningkatkan upaya untuk mempromosikan makanan halal dengan melibatkan masyarakat lokal, termasuk non-Muslim.Kata kunci: Wisata halal; kuliner halal; masyarakat non muslim